Insights gleaned by measuring patients' stated goals for DBS: More than tremor. (10th January 2017) - Kubu, Cynthia S.; Cooper, Scott E.; Machado, Andre; Frazier, Thomas; Vitek, Jerrold; Ford, Paul J.
Abstract : Objective: To report prospective repeated measures data detailing the perceived benefit of deep brain stimulation (DBS) on the most commonly cited symptom and activity goals identified by patients with Parkinson disease. Methods: Fifty-two participants were recruited from a consecutive series. Participants completed a semi-structured interview soliciting their symptom and behavioral goals and corresponding visual analog scales measuring perceived symptom severity and limits to goal attainment. Severity ratings were completed prior to and at 2 times following DBS. Changes in severity over time were assessed using a mixed effects linear model. The pattern of relationships between the severity ratings and standard clinical research (SCR) measures routinely administered were examined using Pearson correlations. Results: The most common symptom goals were improvements in tremor, gait, and nonmotor symptoms, whereas the most frequent behavioral goals related to interpersonal relationships, work, and avocational pursuits. Most severity ratings were significantly correlated with each other but not with the SCR measures. Significant improvements were evident on all SCR measures after DBS. Participants' severity ratings for their symptom and behavioral goals improved significantly over time although not all severity ratings changed in the same manner. Conclusions: These data illustrate that improvements in participants' individually defined goals were evident over time and that some of these improvements occurred in areas in which the benefits associated with DBS are not as well-documented. The participants' severity ratings were not redundant with SCR measures, suggesting that novel and potentially important information can be gleaned by systematically assessing patients' goals.